Pengaruh Lingkungan Kerja dan Komitmen Organisasi Terhadap Produktivitas Kerja Karyawan Produksi CV. Ar-Royyan Group Tasikmalaya - Selfiani (PT Maju Malaqbi Makkarana, 2023)
This study aims to determine the effect of the Work Environment and Organizational Commitment on Employee Productivity in the Production Department at CV. Ar-Royyan Group Tasikmalaya. The method used is a quantitative approach with a sample of 63 respondents from the production employees of CV. Ar-Royyan Group Tasikmalaya. The data used are Primary Data and Secondary Data. The data analysis tool used was multiple linear regression analysis using SPSS version 26. The results showed that simultaneously the Work Environment and Organizational Commitment had a significant effect on Employee Productivity. Partially, the work environment has a significant effect on employee productivity. Partially, Organizational Commitment has a significant effect on Employee Productivity.